d) 4^x+2+4^x+1+4^x/21=3^2x+3^2x+1+3^2x+3/31
help me
a)|-x+2/5|+1/2=3,5 b)21/5+3:|x/4-2/3|=6
c)7,5-3|5-2x|=-4,5 d)1/3-|5/4-2x|=1/4
e)21/5+3:|x/4-2/3|=6
a)|-x+2/5|+1/2=3,5 b)21/5+3:|x/4-2/3|=6
c)7,5-3|5-2x|=-4,5 d)1/3-|5/4-2x|=1/4
e)21/5+3:|x/4-2/3|=6
a: Ta có: \(\left|\dfrac{2}{5}-x\right|+\dfrac{1}{2}=3.5\)
\(\Leftrightarrow\left|x-\dfrac{2}{5}\right|=3\)
\(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{2}{5}=3\\x-\dfrac{2}{5}=-3\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{17}{5}\\x=-\dfrac{13}{5}\end{matrix}\right.\)
b: Ta có: \(\dfrac{21}{5}+3:\left|\dfrac{x}{4}-\dfrac{2}{3}\right|=6\)
\(\Leftrightarrow3:\left|\dfrac{1}{4}x-\dfrac{2}{3}\right|=6-\dfrac{21}{5}=\dfrac{9}{5}\)
\(\Leftrightarrow\left|\dfrac{1}{4}x-\dfrac{2}{3}\right|=\dfrac{5}{3}\)
\(\Leftrightarrow\left[{}\begin{matrix}\dfrac{1}{4}x-\dfrac{2}{3}=\dfrac{5}{3}\\\dfrac{1}{4}x-\dfrac{2}{3}=-\dfrac{5}{3}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\dfrac{1}{4}x=\dfrac{7}{3}\\\dfrac{1}{4}x=-1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{28}{3}\\x=-4\end{matrix}\right.\)
\(\frac{4^{x+2}+4^{x+1}+4^x}{21}=\frac{3^{2x}+3^{2x+1}+3^{2x+2}}{31}\)
Ta có:
\(\frac{4^{x+2}+4^{x+1}+4^x}{21}=\frac{4^x\cdot\left(4^2+4+1\right)}{21}=\frac{4^x\cdot21}{21}=4^x\)
\(\frac{3^{2x}+3^{2x+1}+3^{2x+2}}{31}=\frac{9^x\cdot\left(1+3+3^2\right)}{31}=\frac{9^x\cdot13}{31}\)
Xét \(4^x=\frac{9^x\cdot13}{31}\)
=> \(\frac{4^x}{9^x}=\frac{13}{31}\)
Vì \(\hept{\begin{cases}\left(4;9\right)=1\\13\notin B\left(4\right)\\31\notin B\left(9\right)\end{cases}\Rightarrow x\in\varnothing}\)
Vậy x không tồn tại
tìm x
a, | 5/4x - 7/2 | - | 5/8x + 3/5 | = 0
b, 21/5 + 3 : | x/4 - 2/3 | = 6
c,| 9 + x | = 2x
d, | 2x - 3 | + x = 21
e, | 7 - 2x | + 7 = 2x
f, | -x + 2/5 | + 1/2 = 3,5
G, | 3x - 4 | + 4 = 3x
a) | 5/4x -7/2| - | 5/8x + 3/5| = 0
|5/4x - 7/2| = | 5/8x + 3/5|
TH1: 5/4x - 7/2 = 5/8x + 3/5
=> 5/4x - 5/8x = 3/5 +7/2
5/8x = 41/10
x = 41/10:5/8
x = 164/25
TH2: 5/4x - 7/2 = -5/8x - 3/5
=> 5/4x + 5/8x = -3/5 +7/2
15/8x = 29/10
x = 29/10 : 15/8
x = 116/75
KL: x = 164/25 hoặc x = 116/75
các bài cn lại b lm tương tự nha! h lm dài lắm!
Tìm x, biết :
a, ( x +2 ) ( x^2 - 2x + 4 ) - x( x + 3 ) ( x - 3) = 26
b, ( x - 3 ) ( x^2 + 3x + 9 ) - x( x - 4 ) ( x + 4 ) = 21
c, ( 2x -1 ) ( 4x^2 + 2x + 1 ) - 4x(2x^2 - 3 ) = 23
a/\(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x+3\right)\left(x-3\right)=26\)
↔ \(x^3+2^3\)\(-x\left(x^2-3^2\right)\)= 26
↔\(x^3+8-x^3+9x=26\)
↔\(9x=18\leftrightarrow x=2\)
Vậy x=2
b/\(\left(x-3\right)\left(x^2+3x+9\right)-x\left(x-4\right)\left(x+4\right)=21\)
\(\Leftrightarrow x^3-3^3-x\left(x^2-4^2\right)=21\)
\(\Leftrightarrow x^3-9-x^3+16x=21\)
\(\Leftrightarrow16x=30\)
\(\Leftrightarrow x=\frac{15}{8}\)
Vậy \(x=\frac{15}{8}\)
c/\(\left(2x-1\right)\left(4x^2+2x+1\right)-4x\left(2x^2-3\right)=23\)
↔\(\left(2x\right)^3-1^3-4x\left(2x^2-3\right)=23\)
↔\(8x^3-1-8x^3+12x=23\)
↔\(12x=24\leftrightarrow x=2\)
Vậy x=2
a, (x + 2)(x2 - 2x + 4 ) - x(x + 3)(x - 3) = 26
<=> x3 + 8 - x(x2 - 9) = 26
<=> x3 + 8 - x3 + 9x = 26
<=> 9x - 18 = 0
<=> 9x = 18
<=> x = 2
b, (x - 3)(x2 + 3x + 9) - x(x - 4)(x + 4) = 21
<=> x3 - 27 - x(x2 - 16) = 21
<=> x3 - 27 - x3 + 16x = 21
<=> 16x - 48 = 0
<=> 16x = 48
<=> x = 3
c, (2x - 1)(4x2 + 2x + 1) - 4x(2x2 - 3) = 23
<=> 8x3 - 1 - 8x3 + 12x = 23
<=> 12x - 24 = 0
<=> 12x = 24
<=> x = 2
\(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x+3\right)\left(x-3\right)=26\)
\(< =>x^3-2x^2+4x+2x^2-4x+8-x\left(x^2-9\right)-26=0\)
\(< =>x^3+8-x^3+9x-26=0\)
\(< =>9x-18=0< =>x=2\)
Help me
A) 2x³+6x²=x²+3x
B) (2x+5)²=(x+2)²
C) x²-5x+6=0
D) (2x-7)²-6(2x-7)(x-3)=0
E) (x-2)(x+1)=x²-4
G) 2x(2x-3)=(3-2x)(2-5x)
H) (1-x)(5x+3)=(3x-7)(x-1)
F) (x+6)(3x-1)+x+6=0
I) (4x-1)(x-3)=(x-3)(5x+2)
K) (x+4)(5x+9)-x-4=0
H) (x+3)(x-5)+(x+3)(3x-4)=0
tìm x
a, | 5/4x - 7/2 | - | 5/8x + 3/5 | = 0
b, 21/5 + 3 : | x/4 - 2/3 | = 6
c,| 9 + x | = 2x
d, | 2x - 3 | + x = 21
e, | 7 - 2x | + 7 = 2x
f, | -x + 2/5 | + 1/2 = 3,5
G, | 3x - 4 | + 4 = 3x
a: =>|5/4x-7/2|=|5/8x+3/5|
=>5/4x-7/2=5/8x+3/5 hoặc 5/4x-7/2=-5/8x-3/5
=>5/8x=41/10 hoặc 15/8x=29/10
=>x=164/25 hoặc x=116/75
b: =>3:|x/4-2/3|=6-21/5=9/5
=>|1/4x-2/3|=5/3
=>1/4x-2/3=5/3 hoặc 1/4x-2/3=-5/3
=>1/4x=7/3 hoặc 1/4x=-1
=>x=28/3 hoặc x=-4
c: \(\Leftrightarrow\left\{{}\begin{matrix}x>=0\\\left(2x-x-9\right)\left(2x+x+9\right)=0\end{matrix}\right.\Leftrightarrow x=9\)
e: =>|2x-7|=2x-7
=>2x-7>=0
=>x>=7/2
tìm x biết
a) (6x-3) (2x+4) + (4x-1) (5-3x) = -21
b) 6x (3x+5) - 2x (9x-2) + (17-x) (x-1) + x (x-18) =0
c) (15-2x) (4x+1) - (13-4x) (2x-3) - (x-1) (x+2) + x2=52
d) (8x-3) (3x+2) - (4x+7) (x+4) = (2x+1) (5x-1) - 33
Rút gọn hết ta được :
a/ 41x - 17 = -21
=> 41x = -4 => x = 4/41
b/ 34x - 17 = 0
=> 34x = 17
=> x = 17/34 = 1/2
c/ 19x + 56 = 52
=> 19x = -4
=> x = -4/19
d/ 20x2 - 16x - 34 = 10x2 + 3x - 34
=> 10x2 - 19x = 0
=> x(10x - 19) = 0
=> x = 0
hoặc 10x - 19 = 0 => 10x = 19 => x = 19/10
Vậy x = 0 ; x = 19/10
Rút gọn hết ta được :
a/ 41x - 17 = -21
=> 41x = -4 => x = 4/41
b/ 34x - 17 = 0
=> 34x = 17
=> x = 17/34 = 1/2
c/ 19x + 56 = 52
=> 19x = -4
=> x = -4/19
d/ 20x 2 - 16x - 34 = 10x 2 + 3x - 34
=> 10x 2 - 19x = 0
=> x(10x - 19) = 0
=> x = 0 hoặc 10x - 19 = 0
=> 10x = 19
=> x = 19/10
Vậy x = 0 ; x = 19/10
a) ( 6x - 3 ) ( 2x + 4 ) + ( 4x - 1 ) ( 5 - 3x ) = -21
<=> 12x2 + 24x - 6x - 12 + 20x - 12x2 - 5 + 3x = -21
<=> 41x = -21 + 12 + 5
<=> 41x = -4
<=> x = -4/41
Tìm x:
a)12/16 = -x/4 = 21/y = z/80
b) 1/3.x+2/5.(x-1)=0
c) (2x-3).(6-2x)=0
d) -2/3-1/3.(2x-5)= 3/2
e) 2|1/2.x-1/3|-3/2=1/4
f) 1/3.x-1/2=4 và 1/2 (Hỗn số ý '^')
Tìm x:
b) 1/3.x+2/5.(x-1)=0
\(<=> \dfrac{1}{3} .x +\dfrac{2}{5}x - \dfrac{2}{5} =0\)
\(<=> \dfrac{11}{15}x = \dfrac{2}{5}\)
\(<=> x= \dfrac{6}{11}\)
Vậy \( x= \dfrac{6}{11}\)
c) (2x-3).(6-2x)=0
\(<=> \begin{cases}
2x-3=0 \\
6-2x=0
\end{cases}\) \(<=> \begin{cases}
2x=3 \\
-2x=-6
\end{cases}\) \(<=>\begin{cases}
x=\dfrac{3}{2} \\
x=3
\end{cases}\)
Vậy \(x=( \dfrac{3}{2} ; 3)\)
d) -2/3-1/3.(2x-5)= 3/2
\(<=> 2x-5= \dfrac{5}{2}\)
\(<=> 2x= \dfrac{15}{2}\)
\(<=> x= \dfrac{15}{4}\)
Vậy \(x= \dfrac{15}{4}\)
f) 1/3.x-1/2=4 và 1/2 (Hỗn số ý '^')
\(<=> \dfrac{1}{3} x -\dfrac{1}{2} = \dfrac{9}{2}\)
\(<=> \dfrac{1}{3}x =5\)
\(<=> x= 15\)
Vậy \(x= 15\)